Music Performance Anxiety in Children and Teenagers: Effects of Perfectionism, Self-Efficacy, and Gender - Dempsey, Erin (Université d'Ottawa / University of Ottawa, 2015)
Music Performance Anxiety is something that has affected a number of musicians and numerous studies have been conducted on performance anxiety in adult musicians. However, research on performance anxiety in children and adolescence is still lacking when compared to literature on adult and music performance anxiety. This study examined the signs and symptoms that children (ages 8-12) and teenagers (ages 13-17) feel and the levels of performance anxiety they perceive. In addition, this study also examined levels of perfectionism, self-efficacy and gender as predictors of anxiety and compared these with levels of anxiety. Sixty-five participants completed three questionnaires and a demographic survey. Results suggest a tentative increasing relationship between music performance anxiety and age while no relationship between gender and anxiety was found. Strong relationships between perfectionism and self-efficacy with anxiety indicate that students with high levels of perfectionism and low levels of self-efficacy are more likely to have high levels of performance anxiety. Just as previous studies with adults have found, our findings in children and adolescents suggest that perfectionism may render people vulnerable to performance anxiety while self-efficacy may be an important buffer against this anxiety.
Keywords: music; performance anxiety; children; teenagers; self-efficacy; perfectionism